2016
DOI: 10.1515/med-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Development of epidermal growth factor receptor tyrosine kinase inhibitors against EGFR T790M. Mutation in non small-cell lung carcinoma

Abstract: AbstractIndividualized therapies targeting epidermal growth factor receptor (EGFR) mutations show promises for the treatment of non small-cell lung carcinoma (NSCLC). However, disease progression almost invariably occurs 1 year after tyrosine kinase inhibitor (TKI) treatment. The most prominent mechanism of acquired resistance involves the secondary EGFR mutation, namely EGFR T790M, which accounts for 50%–60% of resistant tumors. A large amount of studies have focused on the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Both drugs exhibited high inhibitory activity against wild-type and mutant EGFR. However, they ultimately develop resistance due to secondary mutations (Wang et al, 2016).…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…Both drugs exhibited high inhibitory activity against wild-type and mutant EGFR. However, they ultimately develop resistance due to secondary mutations (Wang et al, 2016).…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…Use of first generation kinase inhibitors such as erlotinib and gefitinib lead to development of drug resistance and in nearly 50% of NSCLC cases the resistance to TKI therapy is due to the presence of T790M mutation [ 36 ]. We wanted to evaluate whether compound 18 has any effect on the T790M mutation and has any synergistic effect with erlotinib on different cancer cell lines including NCI-H1975 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome T790M-mediated resistance, third-generation EGFR TKIs (osimertinib, olmutinib and rociletinib) have been developed. These agents target T790M, re-sensitizing cancer cells to EGFR TKI inhibition [ 93 , 96 , 97 , 98 ]. A recent report of AURA-3 in a randomized phase III clinical trial revealed that osimertinib represents the standard therapy in NSCLC with EGFR -activating mutation after the failure of first-line EGFR-TKIs compared to platinum-based chemotherapy [ 99 ].…”
Section: Egfr Targeted Cancer Therapy Resistance and Overcoming Rementioning
confidence: 99%